Recycling value materials from waste PCBs focus on electronic components: Technologies, obstruction and prospects. Issue 5 (October 2022) - Wu, Changfa; Awasthi, Abhishek Kumar; Qin, Wenqing; Liu, Wei; Yang, Congren
Abstract: The progress of science and technology speeds up the upgrading of electrical and electronic equipment, resulting in the generation of electronic waste (e-waste). Electronic components (ECs) mount on printed circuit board (PCBs) containing high percent of precious metals, are an indispensable part of e-waste. In this article, integrated and systematic processes adopted for metallic recovering from waste ECs (WECs) were critically reviewed. Disassembly is the first step in recycling of WECs. Various automatic disassembly technologies and subsequent intelligent classification processes were introduced firstly. As a pretreatment step, metals enrichment plays a significant role in upgradation and efficient metal recovery, via physical, pyrolysis, supercritical fluid, and combined technologies. With the confirmed superiority of economic and effective, pyrometallurgical process (smelting-refining) has been conducted at a commercial scale. Hydrometallurgical process with chemical leaching and bioleaching are introduced. Various approaches and techniques for metal elements selective recovery from the leachates including ionic liquids, solvent extraction, electrowinning, adsorption, and precipitation are illustrated. Finally, a complete framework for recycling WECs is established. This study provides guidance for the development of clean and efficient recycling technology of WECs and mitigate various scientific and technological challenges for the e-waste recycling in the circular economy. Graphical Abstract: ga1 Highlights: Various WECs and the disassembly techniques have been introduced. Physical, pyrolysis and supercritical fluid methods are discussed. Pyrometallurgical and hydrometallurgical processes for WECs recovery are summarized. Advantages, obstruction and prospects of various technologies are also analyzed.